A study of structural lineaments in Pantanal (Brazil) using remote sensing data - PARANHOS FILHO,ANTONIO C. (2013)
This paper presents a study of the structural lineaments of the Pantanal extracted visually from satellite images (CBERS-2B satellite, Wide Field Imager sensor, a free image available in INTERNET) and a comparison with the structural lineaments of Precambrian and Paleozoic rocks surrounding the Cenozoic Pantanal Basin. Using a free software for satellite image analysis, the photointerpretation showed that the NS, NE and NW directions observed on the Pantanal satellite images are the same recorded in the older rocks surrounding the basin, suggesting reactivation of these basement structural directions during the Quaternary. So the Pantanal Basin has an active tectonics and its evolution seems to be linked to changes that occurred during the Andean subduction.